Frequency Dependence of Tension–Tension Fatigue in Woven Kevlar/Epoxy: Normalized S–N and Basquin Parameters at 0°, 23°, and 45° (Journal of Engineering, 2026)
In this study, the combined effect of fiber orientation and loading frequency on tension–tension fatigue behavior of woven Kevlar/epoxy laminates was examined. Specimens with fiber orientations of 0°, 23°, and 45° were fabricated via hand lay-up and tested according to ASTM D3039 and ASTM D3479 standards. Static tensile tests with ultimate tensile strengths (UTS) of 276.1 MPa (0°), 159.2 MPa (23°), and 185.81 MPa (45°) showed clear orientation dependence. Fatigue stresses were normalized using (σmax/UTS), Fatigue experiments were conducted at stress levels ranging from 55%to 90% of (UTS) and at two loading frequencies, 5 and 15 Hz. and the results were interpreted through normalized S–N curves, Basquin regression fits, ANCOVA, life reduction ratio (LRR), and SEM fractography. Increasing the loading frequency displayed reduced fatigue lives at all orientations. The 0° laminate experienced the most consistent frequency effect, with a mean LRR of 0.446 (95% CI: 0.381–0.511). In contrast, the 23° and 45° laminates showed smaller and more stress-dependent reductions, with mean LRR values of 0.186 (95% CI: 0.060–0.312) and 0.162 (95% CI: 0.041–0.284), respectively.  ANCOVA results displayed no statistically significant frequency-induced slope differences (p > 0.05) for any orientation, indicating that the fatigue-life decay rate remained unchanged. However, intercept-level effects were practically large at 0° (partial η² = 0.313) and 23° (partial η² = 0.229), reflecting frequency-dependent reductions in fatigue strength. SEM observations also supported these observations, showing more extensive matrix cracking and fiber pull-out at higher frequency. Overall, woven Kevlar/epoxy laminates demonstrated strong anisotropic fatigue behavior, with fiber orientation serving as the dominant factor and frequency acting as a secondary yet influential parameter.